2019
DOI: 10.1049/hve.2019.0030
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of acoustic response from simulated impulsive lightning current discharge

Abstract: Acoustic observation of laboratory simulated lightning discharge can greatly avoid the observation difficulties under natural thunderstorm environment. An acoustic observation experiment based on the impulsive current generation system and a microphone array was carried out and illustrated in this study. A quantitative study on characteristics of response sound pressure initiated from simulated lightning current was performed. The first arrived acoustic N-waves measured at different distances initiated from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…With a higher pulse power and longer inter-electrode gaps, the efficiency decreases. The same result was also obtained on a laboratory lightning simulator [ 17 ]. Some drawbacks of air-coupled devices were highlighted in [ 14 , 15 , 16 , 17 ], namely, the poor directivity of generated acoustic waves and the influence of environmental factors, such as air humidity and the ionization of gas in the inter-electrode space, on the magnitude of amplitude and phase jitter.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…With a higher pulse power and longer inter-electrode gaps, the efficiency decreases. The same result was also obtained on a laboratory lightning simulator [ 17 ]. Some drawbacks of air-coupled devices were highlighted in [ 14 , 15 , 16 , 17 ], namely, the poor directivity of generated acoustic waves and the influence of environmental factors, such as air humidity and the ionization of gas in the inter-electrode space, on the magnitude of amplitude and phase jitter.…”
Section: Introductionsupporting
confidence: 78%
“…The resonance frequencies of the emitter depend on the size and properties of the membrane; however, the discharge itself appears broadband [ 14 , 15 , 16 , 17 ]. Therefore, the development of a membrane model simulating the vibrational characteristics of objects seems to be appropriate in order to minimize the size of experiments and correct some object properties, such as the mass/size ratio and rigidity and/or damping.…”
Section: Measurement Of Vibration Characteristicsmentioning
confidence: 99%
“…Current is a crucial lightning parameter and is important for lightning protection [5]. For instance, it can be used to estimate the charge carried by the leader [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study by [28] investigated the directional characteristics of sparks, and found that the angular position of the microphone affects the widths and peak sound pressures of the received pulses. The authors in [29] observed the acoustic characteristics of lighting current discharge as a function of peak values of discharge currents. Spark characteristics have also been studied for enabling their utilization in studying acoustic phenomena on scale models [7].…”
Section: Literature Reviewmentioning
confidence: 99%